Exploring Teachers’ Instructional Strategies to Facilitate the Oral Fluency of EFL Beginner Level Students - Rizqiyanti, Riza (English Learning Innovation, 2023)
Speaking is a crucial skill in everyday life, encompassing various sub-skills such as oral fluency. However, teaching speaking effectively is a challenging endeavor, as developing good oral fluency requires time and effort. To enhance students' oral fluency, English teachers employ various instructional strategies. To investigate these strategies, the researcher conducted a descriptive study utilizing interviews and observations. The study focused on two English teachers instructing speaking classes at an Islamic private school in Sidoarjo, which offers an International Class program called M-ICO (Muhammadiyah International Class Orientation). The findings revealed that teachers employed student-led activities such as presentations, discussions, and game-based learning to facilitate students' oral fluency; choosing learning materials that can boost students’ oral fluency; using questioning frequently. Additionally, the study identified several speaking difficulties faced by students, such as classroom management issues, linguistic challenges, inhibition, and reliance on their mother tongue. To address these issues, teachers employed strategies such as providing challenges or games, encouraging the use of dictionaries for pronunciation learning, normalizing mistakes, and motivating students during the learning process. In conclusion, teachers adapt their instructional strategies and address concerns based on the unique conditions of their classes. These findings have implications for educators to improve students' oral fluency through strategic approaches. Furthermore, future research should explore the relationship between Islamic values or materials and oral fluency in the context of Islamic school environments.